2019
DOI: 10.1115/1.4043123
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Connectivity-Based Approach for Leakage Channel Prediction in Static Sealing Interface

Abstract: Leakage susceptibility is significant for the functionalization of engineering products, and surface topography plays a crucial role in forming the leakage channel in static sealing interface. This paper proposes a surface connectivity-based approach to predict the leakage channel in static sealing interface. The proposed approach consists of three modules including contact surface generation, leakage parameters definition, and leakage channel prediction. A high-definition metrology (HDM) instrument is adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…21,22 For example, He et al 23 proposed a novel strategy to detect road crack images and enhance the connectivity of fractures by using mathematical morphology. Shao et al 24 developed a surface connectivity-based strategy to evaluate and predict the leakage feature of a static contacting interface. It is worth noting that surface connectivity, as a method of 3D morphological characterization, is also important for exploring the functional properties of surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 For example, He et al 23 proposed a novel strategy to detect road crack images and enhance the connectivity of fractures by using mathematical morphology. Shao et al 24 developed a surface connectivity-based strategy to evaluate and predict the leakage feature of a static contacting interface. It is worth noting that surface connectivity, as a method of 3D morphological characterization, is also important for exploring the functional properties of surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…e metal-to-metal seal is performed by a direct-metal/ metal-tight contact of rough surfaces as shown in Figure 1. Although it is simple in structure, the sealing behavior of a metal-to-metal seal is a ected by a variety of factors [7][8][9][10][11], among which the surface topography, which usually has a microstructure given by machining processes, is thought to be one of the most important factors [12][13][14]. Clearly, engineering materials are known to have rough surfaces, and the full control of surface topography at all scales during manufacturing processes is still out of reach [9].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [12] analyzed the mechanism of static metal sealing, determined the critical condition of the sealing performance, and established the method of calculating the contact pressure of the sealing surface. Shao et al [13] proposed a static seal interface leakage channel prediction method, which included contact generation, leakage parameter definition, and channel prediction, and the experimental results showed that this method could evaluate the static sealing performance well. Lutkiewicz et al [14] proposed a method for evaluating the effectiveness of bolted joint seals based on leakage rate calculation, which took the contact stress graphs, material characteristics, and surface roughness as input and obtained the leakage rate evaluation value.…”
Section: Introductionmentioning
confidence: 99%